Pembatalan Perkawinan Akibat Poligami - Abd. Holik (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2013)
Cancellation of marriage isoneway of breaking the bond of marriagewhose requirement and principle are flawed. In the provisions of article 71 letter (a), the Islamic law compilation says that polygamous marriage can be cancelled if it does not meet the requirement. The main requirement in that provision is there is permit of religious courts. Beside that, in the KHI material making, most of literature used to be base is fiqh shâfi’iyyah idea. So, research about the base of provisions of article 71 letter (a) detterminaion use fiqh shâfi’iyyah. It is library research .Data is analyzed by content analysis. Then, it use descriptive comperative method patterned deductive reasoning. The research concludes that Article 71 letter a KHI is the result of the framers KHI ijtihâd, not legal scholars product shâfi’iyyah. Relevance to the fiqh shâfi’iyyah schools located in the excavation methodology that focuses on the legal aspects of the achievement of beneficiaries and preventive measures on the incidence of damage.